Philosophical Thinking In The Search For The Existence Of A God - Noviansah, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract In this paper discusses the thought of philosophy in seeking the existence of God. So God in human view is very interesting in terms of existence and existence, the reason of man is not able to find and show the presence of human rationally. So that the notoriousness of God from the realm of rational and sought after the existence of it, he bore many major religions in the world, all religions believe that one God is strongest. Then the pilots arose, and the existence of the Lord, that was: 1. Saint Augustine who believed that God was by looking at the history of the drama of Creation, 2. Thomas Aquinas, He combined the thought of Aristotle with Christian Revelation. The truth of faith and the perceived religious experience are able to understand God, 3. Descartes He thought of the Lord commencing from his main principle which is “a combination of Catholic and scientific Pietism”, 4. Immanuel Kant with his methods in seeking the existence of God with his moral law, 5. Alfred North Whitehead He used religious dogma adopted by humans and then sought the truth of the religion from whom. Keywords: Philosophy of Deity, human reason for God, theism as the concept of deity. Abstrak Didalam tulisan ini membahas tentang pemikiran filsafat dalam mencari eksistensi Tuhan. Jadi Tuhan dalam pandangan manusia merupakan hal yang sangat menarik diketahui keberadaanya dan eksistensinya, nalar manusia tidak mampu menemukan dan menunjukan keberadaan manusia secara rasioanal. Sehingga kemsiteriusan Tuhan dari alam rasional ditalar dan dicari eksistensinya olehkarnya ia melahirkan banyak agama-agama besar didunia, semua agama meyakini bahwa satu Tuhan terkuat. Lalu timbullah para filosof yang memikirakan eksistensi Tuhan yaitu: 1.Santo Agustinus yang percaya bahwa Tuhan ada dengan melihat sejarah dari drama penciptaan, 2.Thomas Aquinas dia menggabungka pemikiran Aristoteles dengan Wahyu Kristen. Kebenaran iman dan pengalaman keagamaan yang dirasakan mampu memahami Tuhan, 3.Descartes dia memikirkan Tuhan bermula dari prinsip utamanya yang merupakan “gabungan antara peitisme Katolik dan sains”, 4.Immanuel Kant dengan metodenya dalam mencari eksistensi Tuhan yaitu dengan hukum moralnya, 5.Alferd North Whitehed dia menggunakan dogma-dogma agama yang dianut oleh manusia lalu mencari kebenarannya agama tersebut dari siapa. Kata Kunci : Filsafat Ketuhanan, Alasan Manusia Menalar Tuhan, Teisme Sebagai Konsep Ketuhanan.